Effect of using coccidiosis vaccines and anticoccidia on health and productivity indicators of broiler chickens. - ديوب, يامين; علي نيصافي , (Latakia University Journal -Biological Sciences Series, 2023)
The efficiency of one coccidian vaccine (Paracox-8) and one anticoccidia (Salinomycin) was evaluated in respect of health and productivity indicators of chicken (flesh). One day old chicks were divided into four groups (A-B-C-D). the chicks of each group were weighed on the first day. Group (B) was given coccidian vaccine on the fifth day, Group (C) were given anticoccidia medications, while Group (A) was determined a non-infected control group and (D) was determined an infected control group. Experimental infection was conducted on groups (B-C-D) in around (15000) Oocysts taken from samples infected with mixed coccidiosis, and Group (A) remained a control group. A group of indicators were studied (number of Oocysts, total body weight gain, total amount of consumed food, total percentage of death during the experiment period, total percentage of feed conversion at the end of the experiment period, cross comparison of outcomes to calculate the losses caused by the experimental infection in comparison with the control group and the group given Salinomycin as precautionary measure). The results showed that Group (B) had better outcomes than Groups (C-D) at significances level of (P<0.05) in all procedures while there were no significant differences with Control Group (A).